2015
DOI: 10.1007/s11589-015-0125-0
|View full text |Cite
|
Sign up to set email alerts
|

Localized temporal variation of Earth’s inner-core boundary from high-quality waveform doublets

Abstract: The topography of the inner core is crucial to understand its growth process and interaction with the geodynamo. With the accuracy of teleseismic waveform doublets in determining the travel-time shifts between PKPcd and PKPdf inner-core phases, we examined the temporal change of the inner-core boundary sampled by new earthquake doublets that occurred in the Western Pacific and those previously found from the South Sandwich Islands. The receiver stations are those within the distance range of 128°-142°from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The very slow rotation rate we find is inconsistent with the well‐resolved but spatially localized and inconsistent changes in arrival time of up to 0.5 s identified in waves transmitted through the core, which have Fresnel zones approaching 10° (Tkalčić et al, ; Yao et al, ). This suggests that the changes may well be due to interesting but nonrotational processes in the inner or outer core or both (e.g., (Mäkinen & Deuss, ; Tkalčić et al, ; Xin et al, ; Yao et al, ; Yu, )).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The very slow rotation rate we find is inconsistent with the well‐resolved but spatially localized and inconsistent changes in arrival time of up to 0.5 s identified in waves transmitted through the core, which have Fresnel zones approaching 10° (Tkalčić et al, ; Yao et al, ). This suggests that the changes may well be due to interesting but nonrotational processes in the inner or outer core or both (e.g., (Mäkinen & Deuss, ; Tkalčić et al, ; Xin et al, ; Yao et al, ; Yu, )).…”
Section: Discussionmentioning
confidence: 99%
“…More recent work has gained resolution and examined many more ray paths, but diverged, with some favoring models of accelerating rotation (Lindner et al, 2010) or strongly fluctuating rotations rates (Ding & Chao, 2018;Tkalčić et al, 2013) and others inferring vertical motion of the inner core boundary (Yao et al, 2015) or possibly slurry in the outer core or a few areas of localized deformation (Mäkinen & Deuss, 2011;Xin et al, 2015). Some of the best resolved data sets so far defy interpretation as pure rotation due to inconsistent spatial and temporal patterns (Yao et al, 2019;Yu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Zhang et al (2008) provided more coverage of repeating earthquakes in some subduction zones and concluded that the time‐varying DF arrivals are observable along additional polar paths from Aleutian trench to South Africa and Kuril Island to Brazil. Other efforts to search for temporal changes using the same technique have been carried out (Cao et al, 2007; Song & Dai, 2008; Tkalčić et al, 2013; Wen, 2006; Xin et al, 2015; Yao et al, 2019; Yu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Subtle time shifts or amplitude changes of PKiKP waves within a repeater could reflect temporal changes in ICB depth and its topography[Wen, 2006;Cao et al, 2007;Xin et al, 2015]. Thus, using repeaters can reduce dependence on velocity structures near the ICB.…”
mentioning
confidence: 99%
“…Thus, using repeaters can reduce dependence on velocity structures near the ICB. Subtle time shifts or amplitude changes of PKiKP waves within a repeater could reflect temporal changes in ICB depth and its topography[Wen, 2006;Cao et al, 2007;Xin et al, 2015].…”
mentioning
confidence: 99%